МОВНА І ЕТНОНАЦІОНАЛЬНА ПОЛІТИКА В УКРАЇНІ ЯК СУСПІЛЬНИЙ РИЗИК (Zaporizhzhia Historical Review, 2021)
The paper touches upon the problems of the improvement of legal instruments of language environment in Ukraine in the context of ethnic-national relations and deals with the actual directions of study and optimization of risk realization in different models of state language policy